Shoreline Profile and Changes Monitoring Via Unmanned Aerial Vehicle (UAV) Photogrammetry - Badrul Hisham, Muhammad Hanif; Daud, Mohd Effendi; Mokhtar, Mardiha (Recent Trends in Civil Engineering and Built Environment, 2024)
This research focus on the identification of shoreline profile and its changes. As for this study, the shoreline of Pantai Punggur is selected as the study area. This study was driven by a climate change factors that resulted to a sea level rise and violent behaviour of sea waves. This factor relates to coastal erosion and coastal changes along the west coast of Malaysia. Malaysia's coastline vulnerability on coastal changes is something that is important to be addressed as the location of this country is surround by water and the coastal area plays a big role in the socio-economic activity. In order to understand coastal erosion, it is important to understand about the physical properties of the sediment as well as the knowledge on how it is transported. There are three objective of this study which are to analyze the condition of shoreline at Pantai Punggur using visual inspection method, identify the shoreline beach profile using Pix4D Mapper and Global Mapper software and to identify relationship between beach profile with shoreline changes. Based on the output of this study, all of the listed objective is achieved successfully. In this study, the aerial image capture by the Unmanned Aerial Vehicle (UAV) is process in the software thus determine the shoreline changes based on the processed aerial image. From this research, the shoreline average shoreline changes by Zone A, B, C, D and E is 2.406m, 1.978m, 1.698m, 0.956m and 0.812m.